Phytoseiid mites of the tribe Paraseiulini Wainstein (Acari: Phytoseiidae) from subSaharan Africa - Moraes, G.; Zannou, I.; Ueckermann, E.A.; Oliveira, A.; Hanna, R.; Yaninek, John S. (2008)
This is the eighth publication of a series on the determination of phytoseiid mites of sub-Saharan Africa. Twenty-three phytoseiid species of the tribe Paraseiulini Wainstein are reported in this paper. They refer to all species of this tribe known to occur in sub-Saharan Africa. Six of these species are described for the first time and 13 species are redescribed. Most of the reported species were collected in cassava habitats in tropical Africa and in other habitats in South Africa. A key is included to help in the separation of the species treated in this paper.